Insights into the xylan degradation system of Cellulomonas sp. B6 : biochemical characterization of rCsXyn10A and rCsAbf62A - Garrido, Mercedes Maria (2022)
Valorization of the hemicellulose fraction of plant biomass is crucial for the sustainability of lignocellulosic biorefineries. The Cellulomonas genus comprises Gram-positive Actinobacteria that degrade cellulose and other polysaccharides by secreting a complex array of enzymes. In this work, we studied the specificity and synergy of two enzymes, CsXyn10A and CsAbf62A, which were identified as highly abundant in the extracellular proteome of Cellulomonas sp. B6 when grown on wheat bran. To explore their potential for bioprocessing, the recombinant enzymes were expressed and their activities were thoroughly characterized. rCsXyn10A is a GH10 endo-xylanase (EC 3.2.1.8), active across a broad pH range (5 to 9), at temperatures up to 55 °C. rCsAbf62A is an α-L-arabinofuranosidase (ABF) (EC 3.2.1.55) that specifically removes α-1,2 and α-1,3-L-arabinosyl substituents from arabino-xylo-oligosaccharides (AXOS), xylan, and arabinan backbones, but it cannot act on double-substituted residues. It also has activity on pNPA. No differences were observed regarding activity when CsAbf62A was expressed with its appended CBM13 module or only the catalytic domain. The amount of xylobiose released from either wheat arabinoxylan or arabino-xylo-oligosaccharides increased significantly when rCsXyn10A was supplemented with rCsAbf62A, indicating that the removal of arabinosyl residues by rCsAbf62A improved rCsXyn10A accessibility to β-1,4-xylose linkages, but no synergism was observed in the deconstruction of wheat bran. These results contribute to designing tailor-made, substrate-specific, enzymatic cocktails for xylan valorization.